2014
DOI: 10.1016/j.bbr.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine lesions of the anteromedial ventral striatum impair opposite-sex urinary odor preference in female mice

Abstract: Rodents rely upon their olfactory system to perceive opposite-sex pheromonal odors needed to motivate courtship behaviors. Volatile and nonvolatile components of pheromonal odors are processed by the main (MOS) and accessory olfactory system (AOS), respectively, with inputs converging in the medial amygdala (Me). The Me in turn targets the mesolimbic dopamine system, including the nucleus accumbens core (AcbC) and shell (AcbSh), the ventral pallidum (VP), medial olfactory tubercle (mOT) and ventral tegmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Furthermore, CNO treatment had no effect on vehicle-injected subject mice. These findings, along with previous findings ( Agustín-Pavón et al, 2014 ; DiBenedictis et al, 2014b ), highlight the importance of the VS in the “hardwired” circuitry that underlies behavioral preferences for opposite-sex pheromones—a first step in mate recognition leading to successful reproduction.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Furthermore, CNO treatment had no effect on vehicle-injected subject mice. These findings, along with previous findings ( Agustín-Pavón et al, 2014 ; DiBenedictis et al, 2014b ), highlight the importance of the VS in the “hardwired” circuitry that underlies behavioral preferences for opposite-sex pheromones—a first step in mate recognition leading to successful reproduction.…”
Section: Discussionsupporting
confidence: 79%
“…The VTA provides dopaminergic innervation to the ventral striatum, including the Acb, VP, and OT complex, and neurons in the VTA express Fos in response to opposite-sex chemosignals ( Moncho-Bogani et al, 2005 ; Kang et al, 2009 ; Martel and Baum 2009a ), thereby implicating this region in the processing of salient olfactory information. It has also been shown that dopaminergic modulation of the medial Acb and mOT is necessary for the display of male urinary odor-driven courtship behaviors in estrous female mice ( DiBenedictis et al, 2014b ), further implicating the VTA in pheromone reinforcement. The mOT is a component of the VS, and receives pheromonal input from limbic/amygdaloid structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with DA’s role in learning and reinforcement in other brain regions, OT DA is associated with the formation of learned odor preferences (Zhang, Liu, et al, ). In addition, DAergic neuronal ablation in the medial OT via 6‐OHDA microinjections reduces the preference of sexually naïve female mice to investigate male urinary odors, while having no effect on the ability to discriminate between the odors (DiBenedictis, Olugbemi, Baum, & Cherry, ). Together, these findings suggest that DA in the OT is critical for both learned and innate odor preferences, as well as the primary reinforcing effects of psychostimulants.…”
Section: Dopaminementioning
confidence: 99%